A Therapeutic Role for the F1FO-ATP Synthase. (October 2019) - Nesci, Salvatore; Trombetti, Fabiana; Algieri, Cristina; Pagliarani, Alessandra
Recently, the F1 FO -ATP synthase, due to its dual role of life enzyme as main adenosine triphosphate (ATP) maker and of death enzyme, as ATP dissipator and putative structural component of the mitochondrial permeability transition pore (mPTP), which triggers cell death, has been increasingly considered as a drug target. Accordingly, the enzyme offers new strategies to counteract the increased antibiotic resistance. The challenge is to find or synthesize compounds able to discriminate between prokaryotic and mitochondrial F1 FO -ATP synthase, exploiting subtle structural differences to kill pathogens without affecting the host. From this perspective, the eukaryotic enzyme could also be made refractory to macrolide antibiotics by chemically produced posttranslational modifications. Moreover, because the mitochondrial F1 FO -ATPase activity stimulated by Ca 2+ instead of by the natural modulator Mg 2+ is most likely involved in mPTP formation, effectors preferentially targeting the Ca 2+ -activated enzyme may modulate the mPTP. If the enzyme involvement in the mPTP is confirmed, Ca 2+ -ATPase inhibitors may counteract conditions featured by an increased mPTP activity, such as neurodegenerative and cardiovascular diseases and physiological aging. Conversely, mPTP opening could be pharmacologically stimulated to selectively kill unwanted cells. On the basis of recent literature and promising lab findings, the action mechanism of F1 and FO inhibitors is considered. These molecules may act as enzyme modifiers and constitute new drugs to kill pathogens, improve compromised enzyme functions, and limit the deathly enzyme role in pathologies. The enzyme offers a wide spectrum of therapeutic strategies to fight at the molecular level diseases whose treatment is still insufficient or merely symptomatic.